Emergence of a Carbapenem-Resistant Klebsiella pneumoniae Isolate Co-harbouring Dual blaNDM– 6-Carrying Plasmids in China - Gong, Yali; Lu, Yifei; Xue, Dongdong; Wei, Yu; Li, Qimeng; Li, Gang; Lu, Shuguang; Wang, Jing; Wang, Yunying; Peng, Yizhi; Zhao, Yan (Frontiers in Microbiology, 2022)
The widespread emergence of carbapenem-resistant Klebsiella pneumoniae (CRKP) with limited therapeutic options has become a global concern. In this study, a K. pneumoniae strain called KP2e was recovered from a human case of fatal septic shock in a Chinese hospital. Polymerase chain reaction and sequencing, antimicrobial susceptibility testing, conjugation experiments, S1 nuclease-pulsed field gel electrophoresis/southern blot, whole genome sequencing and comparative genomics were performed to investigate the phenotypic and molecular characteristics of this isolate. KP2e possessed the NDM-6-encoding gene and exhibited resistance to almost all β-lactams except for monobactam. This strain belonged to sequence type 4024, the complete genome of which was composed of one chromosome and three plasmids. Furthermore, blaNDM-6 coexisted on two self-transmissible plasmids, which were assigned to types IncFIB and IncN. A structure of IS26-composite transposon capturing an identical Tn125 remnant (ΔISAba125-blaNDM-6-bleMBL-trpF-dsbC-cutA-groES-ΔgroEL) was identified in the two plasmids, and this conserved blaNDM-surrounding genetic context was similar to that of few IncN plasmids found in other regions of China. Our research appears to be the first description of a clinical strain that emerged co-harbouring dual blaNDM-carrying plasmids, and the first report of NDM-6-positive CRKP in China. These findings demonstrated that IncN is a key medium in the evolution and expanding dissemination of blaNDM genes among various species, which indicates that close monitoring and rapid detection of blaNDM-harbouring plasmids is necessary.